Toward the Development of Virtual Surgical Tools to Aid Orthopaedic FE Analyses. (14th December 2009) - Tadepalli Tadepalli, Srinivas C. Srinivas C.; Shivanna Shivanna, Kiran H. Kiran H.; Magnotta Magnotta, Vincent A. Vincent A.; Kallemeyn Kallemeyn, Nicole A. Nicole A.; Grosland Grosland, Nicole M. Nicole M.
Abstract : Computational models of joint anatomy and function provide a means for biomechanists, physicians, and physical therapists to understand the effects of repetitive motion, acute injury, and degenerative diseases. Finite element models, for example, may be used to predict the outcome of a surgical intervention or to improve the design of prosthetic implants. Countless models have been developed over the years to address a myriad of orthopaedic procedures. Unfortunately, few studies have incorporated patient-specific models. Historically, baseline anatomic models have been used due to the demands associated with model development. Moreover, surgical simulations impose additional modeling challenges. Current meshing practices do not readily accommodate the inclusion of implants. Our goal is to develop a suite of tools (virtual instruments and guides) which enable surgical procedures to be readily simulated and to facilitate the development of all-hexahedral finite element mesh definitions.